The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/rcm.4394
|View full text |Cite
|
Sign up to set email alerts
|

Application of matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry for the study of Helicobacter pylori

Abstract: The characteristics of matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry based investigation of extremely variable bacteria such as Helicobacter pylori were studied. H. pylori possesses a very high natural variability. Accurate tools for species identification and epidemiological characterization could help the scientific community to better understand the transmission pathways and virulence mechanisms of these bacteria. Seventeen clinical as well as two laboratory strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
3
19
0
4
Order By: Relevance
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 83%
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 83%
“…These studies were expanded in a 2010 publication examining the application of MALDI-TOF MS for the species-specific identification of H. pylori (235). Using a collection of 2 reference strains and 17 clinical isolates, MALDI-TOF MS analysis was performed with the Bruker BioTyper 2.0 software.…”
Section: Fastidious Gram-negative Bacteriamentioning
confidence: 99%
“…Despite significant differences observed in MALDI spectra analyzed both in this study and previously, the BioTyper database identified all isolates tested as H. pylori. Thus, MALDI-TOF MS was deemed suitable for the identification of H. pylori, even in the case of an organism which exhibits high levels of genetic plasticity (234,235).…”
Section: Fastidious Gram-negative Bacteriamentioning
confidence: 99%
“…Anders als bei den biochemischen Testsystemen handelt es sich beim MALDI-TOF MS-System um ein offenes, bei dem die Datenbank auch vom Anwender eigenst ä ndig erweitert werden kann. Durch entsprechende Erg ä nzungen der Referenz-Spektren der Datenbanken konnte eine nahezu 100 % Identifi zierungsrate von Neisserien [11] , Clostridien [12] , Mycobakterien [13] , Salmonellen [14] , vergr ü nenden Streptokokken [15] und Helicobacter pylori [16] erreicht werden. W ä hrend das MALDI-TOF MS-System im Vergleich zu biochemischen Testsystemen im Bereich der Differenzierung von Enterobakterien, Staphylokokken und Streptokokken vergleichbar gute Ergebnisse liefert, zeigt es deutliche Vorteile bei der Differenzierung von Gram-positiven St ä bchen [17] , Anaerobiern und einigen Nonfermentern [18,19] .…”
Section: Einsatz Der Maldi-tof Massenspektrometrie In Der Mikrobiologunclassified